O Moderno em Santa Maria da Feira: Viana de Lima - Pedro Luís Pinho Soares (2022)
Alfredo Evangelista Viana de Lima (1913-1991) was a pioneer of the ideals of modern architecture in a Portugal marked by censorship, having been one of the founders of the O.D.A.M. and defensor of the modern architecture's principles enunciated in "Charte d'Athènes". In the course of his career of more than 50 years, he was widely awarded, participated in the C.I.A.M., and produced a vast and diversified work, of which we can highlight some examples, such as the Casa Honório de Lima and the Faculty of Economics, both in Porto, the Casa das Marinhas, or even Hospital de Bragança. Viana de Lima also served as a consultant for city council entities, such as Esposende, Bragança, or Santa Maria da Feira. In Santa Maria da Feira, his period of activity began in 1966 and practically followed him until his death, in 1991. Of the various projects developed for Santa Maria da Feira, only the Banco Pinto Magalhães Building (1966), the arrangement of the public garden in Praça Dr. Gaspar Moreira (1966), the new volume of the City Hall (1976) and the Palácio da Justiça were built. Other unbuilt projects were some collective housing buildings, the Tea House on the hillside of the Castle, a Sports Complex on the banks of the Cáster River, and a urbanization plan for the central area of Vila da Feira. Given my personal relationship with the city and the interest in the work of Viana de Lima, of which only a small part of the wide totality is known, it is intended to study these projects in the municipality, in order to contribute to the knowledge about the architect.